The Urgency of Regulation of the Ultra Qui Judicat Principle in Criminal Judgments - Imran, Suwitno Yutye (Jambura Law Review, 2021)
There is a provision for the judge not to impose a sentence on the defendant if the act is not described carefully, clearly, and ultimately in the public prosecutor's indictment. However, in practice in the court, some judges deviate from the articles charged by the Public Prosecutor. Therefore, this article will analyze the urgency of regulating the ultra qui judicat principle in criminal case decisions. The analysis will be carried out using a normative legal research method using a case approach and data sources from laws and regulations, judges' decisions. The analysis results show that the concrete regulation of the ultra qui judicat principle in the form of legal norms in the Judicial Power Act will benefit judges in deciding cases. The Public Prosecutor's inaccuracy in preparing the indictment, especially the placement of the articles indicted, will be very detrimental to law enforcement and injure the judge's justice in deciding the case. On the other hand, if this principle is not regulated concretely in legal norms, it will open up space for many dissenting opinions on the judge's decision.